Antibody persistence and safety and immunogenicity of a second booster dose nine years after a first booster vaccination with a reduced antigen diphtheria-tetanus-acellular pertussis vaccine (Tdap) in adults. Issue 42 (8th October 2018) - Brandon, Donald; Kimmel, Murray; Kuriyakose, Sherine O.; Kostanyan, Lusiné; Mesaros, Narcisa
Highlights: In vaccinated adults, pertussis antibody levels wane over time, but a Tdap dose boosts immunity. Diphtheria and tetanus seroprotection rates were high 5 (≥98.0%) and 9 (≥98.1%) years post-initial vaccination. Nine years post-vaccination, ≥84.9% of participants were seropositive for pertussis antigens. A dose of Tdap administered 9 years post-primary dose was immunogenic and well-tolerated. Abstract: Background: Over the last decades, pertussis showed periodic increases in its incidence among adults, despite being a vaccine-preventable disease. Methods: This phase III, multicenter, extension study (NCT00489970) was conducted in adults from the United States, followed at Year (Y) 5 and Y9 post-vaccination with a dose of reduced-antigen-content tetanus-diphtheria-acellular pertussis vaccine containing either 3 (Tdap-B group) or 5 pertussis components (Tdap-A group). Willing participants in Tdap groups and newly-recruited participants (Control group) received one Tdap-B dose at Y9. Antibody persistence (at Y5 and Y9) and safety of Tdap-B at Y9 were assessed. Non-inferiority of immune response elicited by 2 Tdap doses was evaluated at Y9: (i) versus one Tdap-B dose for diphtheria and tetanus in terms of seroprotection rates; (ii) for all antigens in terms of booster response rates (Tdap-B and Tdap-A groups versus Control group); and (iii) for pertussis antigens in terms of geometric mean concentrations (GMCs) versus a 3-dose series of a combined diphtheria-tetanus-acellular pertussis vaccine (DTPa) administered during infancy. Results: 1257 participants were enrolled at Y5 and 809 participants were vaccinated at Y9. Seroprotection rates in both Tdap groups were ≥98.4% and ≥98.0% (Y5) and ≥98.3% and ≥98.1% (Y9) for diphtheria and tetanus, respectively. For pertussis antigens, antibody concentrations above assay cut-offs were observed for ≥76.6% (Y5) and ≥84.9% (Y9) of participants in Tdap groups. At Y9, one month post-Tdap vaccination, comparable seroprotection/seropositivity rates and antibody GMCs were observed among groups. Non-inferiority of immune responses in both Tdap groups was demonstrated when compared to the Control group for diphtheria and tetanus and to a 3-dose DTPa series for pertussis antigens. Non-inferiority criteria in terms of booster response were not met for all antigens. No safety concerns were raised. Conclusion: A second dose of Tdap-B administered in adults, 9 years after initial Tdap vaccination, is immunogenic and well-tolerated.